Les trois sagesses de Baruch: Hypothèses sur la figure des Géants en Ba 3, 24-28 - Berterottière, Raphaëlle (Advances in ancient Biblical and Near Eastern research, 2021)
Bar 3:24-28 correlates in a most creative way the downfall of the giants with the wisdom thematic: the giants perished because they were refused the gift of divine wisdom. Their depiction echoes both the offspring of the "sons of God" in Gen 6 and the mighty Canaanites, to indicate two erroneous paths towards wisdom. The thorough rewriting of Gen 6 is especially interesting: contrary to the Genesis account, the birth of the giants is located in the "house of God", a place that seems to outreach human understanding. The purpose of the author may be to distance himself from texts that describe the mysteries of the universe, such as the Book of Watchers. On the other hand, the military competence of the giants associates them with the nations and therefore excludes them from election. Since the text was presumably written in the Hellenistic era, it is not unlikely that this gentile wisdom might be identified with Greek culture. In opposition to these countermodels, the true wisdom, also outlined in the rest of the section, is a divine gift to the whole people of Israel.